중국의 인삼산업 실태와 관련제도 - 이동필 (한국농촌경제연구원, 2006)
The purpose of this study is identify current situations and related institutions for production, processing, marketing, trade, and consumption of ginseng in China. China holds 70% of cultivated ginseng market and 75% of wild Asian ginseng and American ginseng are grown in China. Cultivated areas for the Asian ginseng is 4,500ha while that of the American ginseng is 900ha and wild simmulated ginseng is 16,000ha in 2004. Ginseng 545kg is produced with 8,554 RMD cost for Asian ginseng while 398kg is produced with 2,645 RMD cost of American ginseng in 200 pyeong. This is the reason for rapid increasing area for American ginseng in China. (2) Final ginseng products are classified as two types; root type products(like red ginseng, white ginseng, etc.) and more delicate secondary products(like tea, drink, powder, extract, etc.). Basically, Asian ginseng has been used for root type products while American ginseng has been used for secondary products. The root product has been treated as traditional medicine and the secondary product as functional food in China. Most ginseng shipped to the market including drug store, supermarket, and retailer after processing at local small factory. Because of small factory in processing capacity and capital, quality of ginseng product was doubted at market. In addition, there are well-known brand as 'Shingaiha' and 'Hwangbongsam', but most company do not have their own brands at all. Imitation of the Korea Ginseng brand in China market is one of the most serious problems for the development of marketing. (3) China's ginseng export was increased from 1,700 MT in 2000 to 2,360 MT in 2005 and price per kilogram of ginseng export also was increased from US $6.62 to $12.46 at the same periods. But the export price has been decreased from US $40~50/kg since 1988 because of over production and dumping export with excess competition around 1990s. However, ginseng price is on the rising trend in these years because ginseng production has been decreased in China. Ginseng import was decreased from 3 thousands metric tons(US $34 million) of American ginseng in 2001 to 1,737 tons in 2004 because China succeeded to steady production of the American ginseng in recent years. The Asian ginseng was imported only 15 tons from North Korea and 2 tons from South Korea in 2004. The limited importation of the Asian ginseng is the result of high non-tariff barriers of China. (4) One third of produced ginseng is exported, and residuals are consumed at domestic market in China. About half of the domestic consumption goes to raw materials for medicine, health foods, extract, and cosmetics, etc., and another half goes to personal consumption in the manner of steaming or boiling as tea, and soup for dietary supplement. Chinese people used the Korea ginseng as medicine while the American ginseng was used as foods to support their health like dietary supplement. Although many Chinese believe superiority of the Korea ginseng, it is difficult to consume it because of high price of the Korean ginseng. (5) Although Jilin province produces about 80% of total ginseng production of China, quality of the ginseng has been unstable because of low level of technologies for production and processing. Furthermore, Jilin province did not have famous brand because of insufficient market development efforts. However, Jilin province made public announcement to set 15,000 million RMD ginseng production and US $300million ginseng export as target in 5 years. For the purpose of meeting this target, various policy programs including preperation of production base, promotion of leading ginseng companies, development of hi-tech ginseng product, and establishment of the 'Changbaisan' brand, etc.. (6) According to the findings of this study, followings are suggested as implications for the development of Korean ginseng industry: (i) develop various and convenient ginseng products to meet consumer's needs, (ii) promote wild simulated ginseng industry, (iii) introduce standardization of ginseng production and processing, (iv) establish national ginseng brand, and control quality through the production and marketing process of ginseng, and (v) reform the institution and administration system for the strategic development of ginseng industry in Korea. Researcher: Dong-Phil Lee E-mail address: ldphil@krei.re.kr